1999
DOI: 10.1046/j.1440-1746.1999.01949.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of oesophagogastric varices in patients with liver cirrhosis

Abstract: Background : All patients with liver cirrhosis are recommended for evaluation of oesophagogastric varices (EGV) regularly. This prospective study was designed to develop a predictive model for EGV in cirrhotic patients. Methods : Ninety‐two patients were recruited. From all patients studied, the size of palpable spleen, liver chemistry value, platelet count, prothrombin time, diameter of main portal vein and splenic length as assessed by ultrasonography were determined. Upper endoscopy was performed. Oesopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
56
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 22 publications
7
56
0
3
Order By: Relevance
“…Ng et al, 14 found a mean PVD of 10.5 ± 2.6 mm among patients without esophageal varices and mean PVD of 11.5 ± 2.4 mm among patients with varices. The average PVD was 11.78 ± 1.58 mm in non-variceal group and 14.05 ± 2.26 mm in variceal group( p <0.01) by Shanker et al 15 The best cutoff of PVD for prediction of esophageal varices for our study population was >12.25 mm (Sensitivity = 92.72%, Specificity = 90%).…”
Section: Resultsmentioning
confidence: 94%
“…Ng et al, 14 found a mean PVD of 10.5 ± 2.6 mm among patients without esophageal varices and mean PVD of 11.5 ± 2.4 mm among patients with varices. The average PVD was 11.78 ± 1.58 mm in non-variceal group and 14.05 ± 2.26 mm in variceal group( p <0.01) by Shanker et al 15 The best cutoff of PVD for prediction of esophageal varices for our study population was >12.25 mm (Sensitivity = 92.72%, Specificity = 90%).…”
Section: Resultsmentioning
confidence: 94%
“…It may be explained according to the issue that palpable spleen as well as LEV may both be related to the presence of a higher portal pressure. Different factors found to be important for this purpose included splenomegaly [23][24][25][26][27][28] , thrombocytopenia [23][24][25][26][27][28][29][30] , ascites [25,27] , hepatic encephalopathy [25] , serum albumin concentration [30] , serum bilirubin levels [30] , and Child-Pugh score [27,28] . Thus, the results of our study are consistent with those of the previously published data.…”
Section: Resultsmentioning
confidence: 99%
“…The gold standard in the diagnosis of varices is esophagogastroduodenoscopy (18), but it is an invasive and costly diagnostic procedure. Therefore, several studies (1,15,(19)(20)(21)(22)(23)(24)(25)(26) have addressed the issue of identifying patients with varices by noninvasive or minimally invasive means, with the aim of avoiding endoscopy in those at low risk of having varices. Platelet count and spleen size were the most frequently explored noninvasive parameters.…”
Section: Resultsmentioning
confidence: 99%